SUSTAINABILITY IN PROJECT MANAGEMENT a functional approach. - Brzozowska, Anna; Pabian, Arnold; Pabian, Barbara ([S.l.] : CRC PRESS, 2021)
This book presents a new approach to the issue of project management, showing how it can be approached through the lens of sustainability. The nature of sustainable project management is not only to achieve economic goals, but also environmental and social ones. Considering project management from the perspective of sustainability is very important because sustainable development cannot keep up with the pace and scale of accumulation of ecological and social problems. The natural potential of the Earth is quickly running low. The global equilibrium between the Earth's ecosystems, which have developed for millions of years, and the human world of production and consumption, becomes disrupted. The focus is on a functional approach to the subject, allowing management and business to implement the methodology discussed. Topics discussed include sustainable planning, sustainable organizing, sustainable leading and sustainable controlling. The authors use their combined experience in the area to inform their novel approach. The book will be especially useful for people who are project managers, members of project teams and other project stakeholders. It may also be a useful reference for scientists and students studying the fields of management, IT and business.
OCLC-licensed vendor bibliographic record.
Keywords: Project management; Sustainability; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Development / Sustainable Development